PRELIMINARY RESEARCH THE EFFECT OF NAA AND BAP ON CALLUS OF BANANA (Musa acuminata L) WITH ADDITION OF FUSARIUM WILT DISEASE FROM Fusarium oxysporum f.sp.cubense (Foc) - Bilter A. Sirait; Nur Synta Napitupulu; Agnes Imelda Manurung (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
THE EFFECTS OF NAA AND BAP ON Callus OF BANANA (Musa acuminata L) WITH THE ADDITION OF FUSARIUM WILT DISEASE FROM Fusarium oxysporum f.sp.cubense (Foc). This research was conducted on January to June 2016, at Tissue Culture Laboratory of Dinas Tanaman Pangan dan Hortikultura of North Sumatera Province, Jl.Karya Jasa No.6 Gedung Johor, Medan. The purpose of this research is to know the response of banana barangan callus (Musa acuminate L.) to fusarium (Fusarium oxysporum f. Sp.Cubens). The living callus is subsequently subcultured for organogenesis purposes by treatment of NAA and BAP. The research use Completely Random Design with two factors that is NAA and BAP. NAA consists of 3 levels: N1 = 1 ppm, N2 = 1.5 ppm and N3 = 2 ppm. The second factor using BAP consists of 3 levels: BA1 = 1.5 ppm, BA2 = 3 ppm and BA3 = 3.5 ppm. The results showed that the percentage of live callus after fusarium addition was only 33.33%, interaction of NAA and BAP did not significantly affect the percentage of live plantlets and wet weight of banana plantlet. The highest percentage of live plantlet on aged 9 - 13 week after subculture and the highest wet weight of planlet found on N1(1 ppm) each 7.05 % and 3.62 g, while the highest percentage of live plantlets on aged 9 - 13 Week after subculture and the highest wet weight of plantlet found on BA1 (1,5 ppm) each 5.69 % and 3.38 g. The treatment combinations that gave the highest percentage of planlets live and wet weight of planlet were N1BA1 and N1BA2.